Imaging stretch-activated firing of spinal afferent nerve endings in mouse colon - travis, Lee; Spencer, Nick (Frontiers in Neuroscience, 2013)
Spinal afferent neurons play a major role in detecting noxious and innocuous stimuli from visceral organs, such as the gastrointestinal tract. However, all our understanding about spinal afferents has been obtained from recordings of spinal afferent axons, or cell bodies that lie outside the gut wall, or peripheral organ they innervate. No recordings have been made directly from spinal afferent nerve endings, which is where sensory transduction occurs. We developed a preparation whereby recordings could be made from rectal afferent nerve endings in the colon, to characterize mechanisms underlying sensory transduction. Dorsal root ganglia (L6-S2) were removed from mice, whilst retaining neural continuity with the colon. Fluo-4-AM was used to record from rectal afferent nerve endings in myenteric ganglia and circular muscle at 36oC. In slack (unstretched) preparations of colon, no calcium transients were recorded from spinal afferent endings. However, in response to a maintained increase in circumferential diameter, a maintained discharge of calcium transients occurred simultaneously in multiple discrete varicosities along single axons of rectal afferents in myenteric ganglia and circular muscle. Stretch-activated calcium transients were resistant to hexamethonium and nifedipine, but were abolished by tetrodotoxin, CPA, BAPTA-AM, cobalt, gadolinium, or replacement of extracellular Na+ with NMDG. In summary, we present a novel preparation in which stretch-activated firing of spinal afferent nerve endings can be recorded, using calcium imaging. We show that circumferential stretch of the colon activates a maintained discharge of calcium transients simultaneously in varicosities along single rectal afferent endings in myenteric ganglia and circular muscle. Non-selective cation channels, TTX-sensitive Na+ channels and both extracellular calcium influx and intracellular Ca2+ stores are required for stretch-activated calcium transients in rectal afferent endings.